Bend-twist coupling effects on the cavitation behavior and hydroelastic response of composite hydrofoils. (January 2023) - Liu, Yunqing; Zhang, Hanzhe; Wu, Qin; Yao, Zhifeng; Huang, Biao; Wang, Guoyu
Highlights: Deduced the effective stiffness of composite hydrofoils with different ply angles. The positive/negative bend-twist effect accelerates/ decelerates the cavitation inception. The positive/negative bend-twist effect decreases/increases the dominant vibration frequency. Abstract: The objective of this work is to investigate the influence of bend-twist coupling effects on the cavitation behavior and hydroelastic response of four hydrofoils with identical geometry: one rigid hydrofoil and three composite hydrofoils of carbon-fiber reinforced plastic (CFRP) with the ply angles of 45°, 0°, and -45°, respectively. A synchronized measurement system consisting of a high-speed camera, a hydrodynamic load cell, and a Laser Doppler Vibrometer is applied to obtain the cavity dynamics and hydroelastic response simultaneously. The theoretical cross-sectional effective bending stiffness, twisting stiffness, and bend-twist coupling stiffness are calculated based on a chordwise-rigid laminated plate model. In addition to the primary cavity shedding frequency and natural frequencies, additional modulated frequencies are excited for all the hydrofoils due to time-varying added mass effects, which broadens the frequency response of the hydrofoil. Re-entrant jet and shockwave mechanisms are identified as instabilities causing periodic cloud cavity shedding. The cloud cavity shedding frequency is found to be independent of cavitation number in certain conditions induced by the shockwave mechanism. Bubbly shock induces a secondary shedding of cloud cavities, causing the reduction of the cavity shedding frequency. The CFRP 45 hydrofoil with a positive bend-twist coupling effect promotes the bending and twisting deformations of the hydrofoil, increasing lift and moment, decreasing the cloud cavity shedding frequency due to the increase in cavity length, and accelerating the cavitation regime transition by reducing cavitation number. And the opposite is true for the CFRP -45 hydrofoil with a negative bend-twist coupling effect.